Chaotic characteristic identification for carbon price and an multi-layer perceptron network prediction model. Issue 8 (15th May 2015) - Fan, Xinghua; Li, Shasha; Tian, Lixin
Highlights Carbon prices are studied from the chaotic point of view. Carbon prices are found to be chaotic rather than stochastic. The multi-layer perceptron network model is based on reconstructed phase space. The MLP model possesses good performance in both level and directional measurement.